Radon Assessment in Ceratophyllum demersum Plant Samples - Al Ani, Rana R; Amin, Sahar A; Alwan, Ahmed (Iraqi Journal of Science, 2022)
The amount of radioactive isotopes in submerged Ceratophyllum demersum plants samples were estimated using passive track detector CR-39. The samples were collected from four selected sites along the Tigris River in Baghdad city, on a monthly basis for one complete year of 2019. Certain factors like radon concentration (Bq.m-3), radium content (Bq.kg-1) and uranium concentration (ppm) were evaluated. The average values of 222Rn level, 226Ra content and 238U concentration in Ceratophyllum demersum samples for site (1) were (593.1 Bq.m-3, 5.8 Bq.kg-1, 0.113 ppm), site (2) were (413.4 Bq.m-3, 3.8 Bq.kg-1, 0.074 ppm), Site (3) were (465.5 Bq.m-3, 4.3 Bq.kg-1, 0.083 ppm) and site (4) were (431.3 Bq.m-3, 3.9 Bq.kg-1, 0.077 ppm), respectively. The results obtained in this work indicated that the radium content and uranium concentration present in the Ceratophyllum demrsum is acceptable which does not pose any risk to the aquatic ecosystem.